Mutation Profiling of Paediatric Solid Tumours in a Cohort of South African Patients - Manolas, Erin (University of the Witwatersrand, Johannesburg, 2023)
Childhood cancers are an emerging global health burden, with the highest increase in incidence and mortality rates occurring in low-middle income countries, such as South Africa (SA). Adding to this burden is the contribution of cancer-predisposing genes (CPGs), whose germline variants increase the risk of cancer development in childhood. These genes are largely associated with a set of disorders, known as cancer-predisposing syndromes (CPSs), which are characterised by an increased likelihood of cancer development and/or additional phenotypic malignant/non- malignant features. Next-Generation Sequencing (NGS) technologies have been key in determining the occurrence and contribution of such germline variants to paediatric cancer development across international research and diagnostic settings. However, these technologies have not been applied to paediatric cohorts in SA and thus there is a paucity of data regarding the contribution of germline variants to childhood cancer development in this setting. Through the design and evaluation of an NGS targeted-CPG panel, this study aimed to generate germline variant profiles of SA paediatric cancer patients, thereby gaining insight into their potential role in the pathogenesis of childhood cancers. NGS was performed on the genomic DNA from 32 solid-tumour paediatric cancer patients using an Ion Ampliseq 50 CPG panel design and the Ion Torrent S5 sequencing instruments. Germline variants were called using the Ion Torrent Suite™ software (v.5.12.0) and annotated using the Ensembl Variant Effect Predictor. Variants were filtered using a bioinformatics pipeline assessing variant data from population and public databases, computational data, functional studies data, genetic pedigrees indicating family history and phenotypic data. Variant evidence was further interpreted for variant prioritisation and classification according to the ACMG-AMP guidelines. All putative pathogenic/likely-pathogenic (P/LP) variants identified were validated via Sanger Sequencing. Seven pathogenic and/or likely pathogenic germline variants were identified and validated in seven patients. Three of these variants, identified in the NF1, RET, and TP53 genes, were detected in patients who presented with phenotypes consistent with their genetic findings and are associated with well-known CPSs (diagnostic yield - 3/32, ~9.4%). The remaining four variants, identified in the BRCA1, ERCC3, FAH, and RB1 genes, have not been previously associated with the patient’s cancer phenotype and therefore require further investigation. At the time of this project’s data generation, this is the first global report of the novel heterozygous, likely pathogenic FAH p.R162H variant. Additionally, although reported elsewhere, the majority of the variants identified in this study (6/7, ~86.7%) have been reported for the first time within the SA paediatric population. To our knowledge, this is the first study to utilise NGS technologies in the germline variant profiling of paediatric solid-tumour patients in SA and therefore has greatly added to filling the current knowledge gap. In addition, these findings have contributed towards the foundation for the development of a CPG sequencing panel suitable for implementation in a SA diagnostic setting
A Dissertation in fulfillment of the requirements for the degree of Master of Science in Medicine (Human Genetics) submitted to the Faculty of Health Sciences , School of Pathology , University of the Witwatersrand, Johannesburg, 2023
Keywords: Germline; Mutation-profiling; Paediatric cancer; Next-Generation Sequencing; Targeted gene panel; UCTD; SDG-3: Good health and well-being